Pengaruh Kompres Hangat Air Serai dan Jahe Merah terhadap Penurunan Intensitas Nyeri Arthritis Rheumatoid pada Lansia - Junelty Almar; Eko Winarto; Julvainda Eka (Syntax Corporation, 2023)
Research Method: This study utilized a quantitative research design with a quasi-experimental research design involving 111 respondents in a pre-test post-test with a control group. Results: The majority of respondents were aged 60-69 years, accounting for 69 respondents (62%), and most had an elementary school education, with 51 respondents (46%). The Wilcoxon test for the pre-test and post-test in the intervention group had a P-Value of 0.000<0.05, while the Wilcoxon test for the pre-test and post-test in the control group had a P-Value of 1.000>0.05. The Mann-Whitney test for the post-test in the Lemongrass and Red Ginger Intervention Group had a P-Value of 0.007<0.05, and the Mann-Whitney test between the intervention and control groups had a P-Value of 0.000<0.05. The Wilcoxon test results showed a P-Value of 0.000 for both the pre-test and post-test. The Lemongrass Warm Compress Intervention related to dignity and comfort had a P-Value of 0.014, while the P-Value for meaning and peace was 1.000. The pre-test and post-test for Red Ginger Warm Compress for pain had a P-Value of 0.000, dignity and comfort had a P-Value of 0.000, and meaning and peace had a P-Value of 0.317. The Wilcoxon test for pain in the pre-test and post-test in the control group had a P-Value of 1.000, and the Mann-Whitney test for the Lemongrass Warm Compress Intervention pre-test and post-test resulted in a mean rank of 29.11, while the Red Ginger Warm Compress pre-test and post-test had a mean rank of 45.89. Conclusion: Warm compresses with lemongrass and red ginger can be used as complementary therapy in addressing pain issues in the elderly with rheumatoid arthritis.